The influence of physical activity on internet addiction among Chinese college students: the mediating role of self-esteem and the moderating role of gender - Du Zhihao; Wang Tao; Sun Yingjie; Zhai Feng (BMC, 2024)
Abstract Objectives The significance of self-esteem in the relationship between physical activity and Internet addiction among college students cannot be over, as it lays a solid foundation for the prevention and control of Internet addiction. Methods A total of 950 college students were surveyed using the Physical Activity Rating Scale (PARS-3), Rosenberg Self-Esteem Scale (SES), and Chinese Internet Addiction Scale (CIAS-R) through a cluster random sampling method. Descriptive statistics, independent sample t-test, partial correlation analysis, mediation effect, moderation effect, and Bootstrap testing were conducted on the collected data to analyze and interpret the results. Results (1) Significant gender differences were found in the amount of physical activity and the degree of Internet addiction among college students(P&& lt;0.001); (2) Physical activity was significantly and positively correlated with self-esteem (r = 0.26, P < 0.001), but significantly and negatively correlated with Internet addiction (r=-0.23, P < 0.001); Meanwhile, self-esteem and Internet addiction were significantly and negatively related to self-esteem (r=-0.22, P < 0.001). (3) Mediating effect analyses showed that self-esteem played a partial mediating role in physical activity and Internet addiction among college students, accounting for a portion of 78.95%. (4) A moderating effect of gender on the relationship between physical activity and Internet addiction was discovered. Conclusion The physical activity level of male students is significantly higher than that of female students, while the degree of internet addiction among female students is notably higher than that of male students. Physical activity can not only directly improve the issue of internet addiction among college students, but also indirectly improve it through self-esteem, with gender playing a moderating role in this process. This conclusion has practical reference significance for preventing and controlling internet addiction among college students, and provides evidence support for using physical activity as a reference solution in clinical applications. Additionally, it suggests that gender should be taken into account when preventing and intervening in internet addiction among college students, and different strategies and methods should be adopted for male and female students. Male students should be encouraged to participate more in physical activities, gradually increasing the frequency, duration, and intensity of their participation, in order to divert their attention and enhance their sense of achievement in sports, thereby reducing their use of mobile phones. For female students, on the other hand, it is important to strengthen real-life communication, change the form of sports participation, engage in group, collaborative, and different situational sports activities, and enhance their focus and attention in sports, in order to reduce their internet dependency, better guide them to use the internet reasonably, and enable them to achieve emotional release through sports.